Financial ratios and fraudulent financial statements: evidence from Malaysian fraud cases / Radziah Mohd Dani - Mohd Dani, Radziah (2013)
This study examines the predictive ability of financial ratios m predicting the likelihood of fraudulent financial statements in Malaysia. Thirteen financial ratios including the classical Altman (1968) Z-score and Beneish (1991) M-score are examined in this study. The sample consists of 122 matched samples of fraud and non-fraud companies and covers an eight-year period of 2003 to 2010. The fraudulent financial statements cases were identified based on the revelation of fraud and lawsuits as well as the breaches of the regulations of Bursa Malaysia and Securities Commission. Using the logistic regression model and relevant diagnostic tests, the findings show that eight financial ratios have significant relationship with fraudulent financial reporting. The significant financial ratios are (i) debt-to-equity, (ii) sales-to-total assets, (iii) sales, general and administration expenses index, (iv) days sales in receivables index, (v), asset quality index, (vi) depreciation index, (vii) sales growth index, and total accruals-to-total assets. The Beneish (1991) m-score is associated with the fraudulent financial statements. This study concludes that financial ratios are useful in predicting the likelihood of fraudulent financial statements in Malaysia. In addition, this study will give benefits to a group of stakeholders that consist of policy makers & standard setters, professionals, investors and researchers on the significance ratios reflect to the fraudulent financial statements.